Frequency of H. Pylori Infection among Dyspeptic Patients and Correlation with Histopathological Evaluation (Medical Forum Monthly, 2023)
Objective: To determine the frequency of H. Pylori infection among dyspeptic patients through histopathological evaluation. Study Design: Descriptive cross-sectional Study Place and Duration of Study: This study was conducted at the Gastroenterology Department of Ziauddin Medical University Hospital in Karachi from November 2, 2022, to May 1, 2023. Materials and Methods: Patients between the ages of 18 and 60 who had dyspepsia and requested an endoscopic biopsy were enlisted. Samples were gathered and transported for histopathological analysis in a formalin bottle. Hematoxylin-eosin was used to stain the section in the histopathology lab. Using SPSS, data analysis was carried out. Data presentation using descriptive statistics. The percentages used to express categorical variables. For a continuous variable, the mean and standard deviation were calculated. H. Pylori infection frequency was given as a percentage. Results: There were 101 females and 95 males. The median age of the group was 39.54 ± 12.91 years. 39 patients had H. Pylori, which was diagnosed. Among the 196 individuals, 79 had mild gastritis while the remaining 117 had moderate gastritis. Thirty (30.6%) male patients and nine (8.9%) female patients had H. Pylori. H. Pylori is highly correlated with gender, although there is no correlation between gender and mild or severe chronic gastritis. H. Pylori was discovered in 13 (21.3%), 9 (22.5%), 6 (13.0%), and 11 (22.4%) patients, respectively, in the age ranges of 18–30, 31–40, 41–50, and 51–60. With regard to age groups and H. Pylori, no meaningful correlation was discovered. The mild chronic gastritis was discovered in 27 (44.3%), 17 (42.5%), 14 (30.4%), and 21 (42.9%) patients, respectively, in the age groups of 18–30, 31–40, 41–50, and 51–60. 34 patients (55.7%), 23 patients (57.5%), 32 patients (69.6%), and 28 patients (75.1%) in the age categories of 18 to 30, 31 to 40, 41 to 50, and 51 to 60 years, respectively, had mild chronic gastritis. Conclusion: According to the study's findings, H. Pylori is very common among dyspeptic patients who were diagnosed using biopsy-based techniques. A sizable section of the Pakistani population is infected with H. Pylori, and the H. Pylori status of a person presenting with disorders that have a strong association with this organism should be taken into consideration.